The social determinants of knowledge and perception on pulmonary tuberculosis among females in Jakarta, Indonesia (Medical Journal of Indonesia, 2014)
Background: Indonesia has not resolved tuberculosis burden since its prevalence and incidence has remained high. As the capital of Indonesia with a large population and a high number of tuberculosis cases, Jakarta has a distinctive condition of tuberculosis burden. This study aimed to obtain social determinants of knowledge and perception of pulmonary tuberculosis in an urban community. Methods: This study used 2,323 samples taken by random sampling in Jakarta during February-May 2011. Questionnaires were delivered to assess respondents’ knowledge and perception about pulmonary tuberculosis. Levels of knowledge were categorized into ‘poor’ and ‘good’. Perceptions about tuberculosis were measured by whether respondents perceived tuberculosis as a humiliating disease and a shunned disease. Results: Most respondents (88.7%) had good level of knowledge about tuberculosis, but misperception remained high (45.9%) in the community. Education level determined level of knowledge. The higher the education level the lower the risk of lack of knowledge. Tuberculosis perceptions were determined by family income and education level. Higher family income and education level were protective factors of misperception about tuberculosis as a humiliating disease and tendency to shun tuberculosis patients. Conclusion: People in urban area of Jakarta have good level of knowledge about tuberculosis, but it does not necessarily lead to proper perception of tuberculosis. Age, education level and having health insurance determined level of knowledge, while tuberculosis perceptions were determined much more by education level and family income. Tuberculosis control program should consider these determinants prior to developing a comprehensive strategy.